MENJEMBATANI KESENJANGAN GENERASI: PENDEKATAN EFEKTIF PEDAGOGIS KRISTIANI DI ERA DIGITAL - Topayung, Semuel Linggi (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2024)
This research utilizes a qualitative method with a case study approach, literature review, and document analysis. It aims to identify the challenges and opportunities within Christian Education in the digital era and to develop innovative strategies for bridging the generation gap between teachers and students.The main issue examined is how to maintain the relevance and effectiveness of Christian Education amidst the development of digital technology. Referring to the identified problem, this research offers the latest concept: a comprehensive integration of digital technology with the pedagogical principles of Christian Education. The pedagogical approach referred to is a Christian Education strategy focused on innovation and creativity in teaching delivery by utilizing digital technology to bridge the generation gap. The results show that this approach is effective in increasing student engagement, creating a conducive learning environment, and supporting the academic and spiritual growth of the digital generation.